Opening the Scientific Expert's Black Box: 'Critical Trust' as a Reformative Principle in Criminal Evidence. (October 2016) - Carr, Sophie; Piasecki, Emma; Tully, Gillian; Wilson, Tim J
The work of forensic scientists, by providing specialist assistance beyond the normal experience or knowledge of the factfinders, can be elusive to the law's traditional probative safeguards. These safeguards, in any case, only apply to the small proportion of such evidence actually tested in court. The specialist nature of the scientific work and the knowledge and understanding needed by users with a non-scientific background makes trust in forensic science problematic if conceptualised in binary terms. A systematic review of the development of the quality controls for the production and use of expert scientific evidence demonstrates that critical trust, as an organising principle, does offer a continuum (ranging from scepticism to acceptance) for assessing the reliability and use of forensic science evidence. Despite progressive reform in forensic science, significant risks remain. These risks are both (i) scientific, including the fragmentation of scientific interpretation and the assurance that all providers and/or processes can meet the necessary standards, and (ii) professional, ranging from the timely provision of information to the ability of counsel to critically test the evidence in a manner intelligible to the factfinders.